Effectiveness of a Novel Smartphone Health Education Intervention in Enhancing Knowledge, Attitudes, and Practices for the Prevention of Respiratory Tract Infections Among Private Hajj Pilgrims From Malaysia - Mohammed Dauda Goni; Mohammed Dauda Goni; Nyi Nyi Naing; Habsah Hasan; Nadiah Wan-Arfah; Zakuan Zainy Deris; Wan Nor Arifin; Aisha Abubakar Baaba; Babagana Mohammed Adam; Muhammad Rafie Arshad (Frontiers Media S.A., 2021)
This study was aimed to develop and evaluate the efficacy of a health education program for increasing knowledge, changing attitudes, and promoting prevention practices to reduce the incidence of RTIs among Malaysian Hajj pilgrims. A quasi-experimental study was done among 130 Hajj pilgrims attending Hajj orientation course organized by a private Hajj tour companies. Hajj pilgrims assigned to intervention group (n = 65) and control group (n = 65). Data were collected baseline and after return from Hajj using a validated questionnaire. Mixed design repeated measure ANOVA was used to analyse the effect of group, time, and group-time interaction on the dependent variables. There was a significant improvement in knowledge, attitude and practice scores in the intervention group compared to the control group. Based on the findings of the interaction of time and group, there was a significant statistical difference for post intervention for knowledge (p = 0.005), attitude (p = 0.041), and practice (p = 0.002). The newly-established health education intervention smartphone application was effective in improving KAP toward RTIs prevention among pilgrims.